Isolation and genetic characterization of MERS-CoV from dromedary camels in the United Arab Emirates - Khalafalla, Abdelmalik Ibrahim; Ishag, Hassan Zackaria Ali; Albalushi, Hamdoon Ismail Abdulla; Al-Hammadi, Zulaikha Mohamed Abdel-Hameed; Al Yammahi, Saeed Mohamed Saeed; Shah, Asma Abdi Mohamed; Al Muhairi, Salama Suhail Mohammed (Frontiers in Veterinary Science, 2023)
The study of coronaviruses has grown significantly in recent years.MERS-CoV replicates in various cell types, and quick development has been made of assays for its growth and quantification. However, only a few viral isolates are now available for investigation with full characterization. The current study aimed to isolate MERS-CoV from nasal swabs of dromedary camels and further molecularly analyze them in order to detect strain-specific mutations and ascertain lineage classification.We isolated the virus in Vero cells and adapted it for in vitro cultivation. The isolates were subjected to complete genome sequencing using next-generation sequencing followed by phylogenetic, mutation and recombination analysis of the sequences.: A total of five viral isolates were obtained in Vero cells and adapted to in vitro cultures. Phylogenetic analysis classified all the isolates within clade B3. Four isolates clustered close to MERS-CoV isolate camel/KFU-HKU-I/2017 (GenBank ID: MN758606.1) with nucleotide identity 99.90% -99.91%. The later isolate clustered close to MERS-CoV isolate Al-Hasa-SA2407/2016 (GenBank ID:This is a provisional file, not the final typeset article Public MN654975.1) with a sequence identity of 99.86 %. Furthermore, the isolates contained several amino acids substitutions in ORF1a (32), ORF1ab (25), S (2), ORF3 (4), ORF4b (4), M (3), ORF8b (1), and the N protein (1). The analysis further identified a recombination event in one of the reported sequences (OQ423284/MERS-CoV/dromedary/UAE-Al Ain/13/2016).Data presented in this study indicated the need for continuous identification and characterization of MERS-CoV to monitor virus circulation in the region, which is necessary to develop effective control measures. The mutations described in this investigation might not accurately represent the virus's natural evolution as artificial mutations may develop during cell culture passage. The isolated MERS-CoV strains would be helpful in new live attenuated vaccine development and efficacy studies.